2021
DOI: 10.1038/s41598-021-91159-6
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and surface topology of activity of pyrazoloquinoline derivatives as corrosion inhibitor on the copper surfaces

Abstract: In the present study, corrosion inhibition performances of some pyrazolo [3,4-b] quinoline-3,5-dione derivatives against the corrosion of copper metal were investigated using B3LYP/6-311++g(d,p) calculation level in aqueous media. Additionally, interaction energies were calculated for all the pyrazoloquinoline derivatives compounds. In the calculations it is observed that studied molecules adsorb on metal surface with the help of electron donor heteroatoms in their molecular structures. Chemical thermodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For a more thorough explanation of the molecular characteristics of dyes, the electron accepting power (ω+), which represents a chemical system's capacity to accept a minute fraction of charge, and the electron donating power (ω−), which represents a chemical system's capacity to release a minute fraction of charge, have been studied [47]. Table 6 includes a list of these parameters.…”
Section: Ionization Potential Electron Affinity and Electrophilicitymentioning
confidence: 99%
“…For a more thorough explanation of the molecular characteristics of dyes, the electron accepting power (ω+), which represents a chemical system's capacity to accept a minute fraction of charge, and the electron donating power (ω−), which represents a chemical system's capacity to release a minute fraction of charge, have been studied [47]. Table 6 includes a list of these parameters.…”
Section: Ionization Potential Electron Affinity and Electrophilicitymentioning
confidence: 99%
“…These quinoline compounds are multipurpose and have a variety of properties, such as anti-HIV, anti-Alzheimer, antibacterial, anti-malarial, antiviral, anti-inflammatory, anti-diabetic, anti-proliferative, antitumor, anti-platelet, anti-leishmanial, anti-tubercular, antioxidant, anticancer, anti-trypanosomal, anti-plasmodial, antimicrobial, anticonvulsant, and corrosion inhibition agents. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Although there are several techniques to build the structural core of quinolines, Friedländer annulation remains one of the most convenient and attractive methods for generating poly-substituted quinolines. Recent reports have described the synthesis of many quinoline analogues utilizing a range of catalysts, including phosphoric acid, GO, Fe 3 O 4 @SiO 2 /ISN/Cu (II), SiO 2 /H 2 SO 4 , [GrBen-zImi]SO 3 H, sulfated polyborate, Mn (CO) 5 Br, and PANEOSF.…”
Section: Introductionmentioning
confidence: 99%
“…The Povarov reaction has grown in significance and utility for the synthesis of quinoline derivatives in contemporary research. These quinoline compounds are multipurpose and have a variety of properties, such as anti‐HIV, anti‐Alzheimer, antibacterial, anti‐malarial, antiviral, anti‐inflammatory, anti‐diabetic, anti‐proliferative, antitumor, anti‐platelet, anti‐leishmanial, anti‐tubercular, antioxidant, anticancer, anti‐trypanosomal, anti‐plasmodial, antimicrobial, anti‐convulsant, and corrosion inhibition agents 15–33 . Although there are several techniques to build the structural core of quinolines, Friedländer annulation remains one of the most convenient and attractive methods for generating poly‐substituted quinolines.…”
Section: Introductionmentioning
confidence: 99%
“…In the current research, we show the design, synthesis, and cytotoxicity evaluation of pyrazolo [4,3-f ]quinoline derivatives as potential anticancer agents (Figure 1). In addition, several studies reported that pyrazoloquinolines synergized in a single nucleus have been linked to a variety of biological actions, including anticancer, antiviral, antibacterial, antimalarial, anti-inflammatory, immunostimulant, and high corrosion inhibition activity [24][25][26][27]. Based on a bioisosterism strategy, this study aimed to generate a string of more active molecules by fusion of our 6,6,6-heterocyclic skeleton-similar previous work and 5,6,6-heterocyclic skeleton-similar anticancer medicines such as camptothecin (Figure 1).…”
Section: Introductionmentioning
confidence: 99%